The relationship between Social Media Addiction, Academic Burnout, and Academic Performance among UKM Undergraduate Students: A preliminary study - Jiao, Caiqi; Fazilah Idris (Penerbit Universiti Kebangsaan Malaysia, 2023)
The main target of the survey was to identify whether the internal and external factors would affect the student’s academic performance. Specifically, to investigate the relationship between social media (SM) addiction, academic burnout, and academic performance among 166 UKM Undergraduate Students. Bergen Social Media Addiction Scale (BSMAS) and Maslach Burnout Inventory – Student Survey (MBI-SS) were used to evaluate the SM addiction level and academic burnout level separately. Grade Point Average (GPA) for the latest Semester was used to measure academic performance. Findings indicated that demographic factors (Gender and Year of Study) have an insignificant relationship with SM addiction and academic burnout. Pearson Correlation denoted academic burnout was significantly correlated with SM addiction and academic performance. Sobel Test showed a significant result of Academic Burnout’s mediating effect between SM addiction and academic performance, which means SM addiction level has an indirect and significant relationship with academic performance. Obviously, SM Addiction aggravates the level of academic burnout among UKM students leading them not to have a good mindset to do academic activities, which performed a drop from an academic perspective. We also perceived the mediating effect of academic burnout may enlighten scholars in the future that to focus on other entertainment like extracurricular activities to alleviate the severity of academic burnout or academic performance downturn. It is suggested universities, tertiary institutes encourage undergraduate students to use social media properly to prevent the malignant circle between SM addiction, academic burnout, and academic performance downturn.